Amelia Erroway : castaway commander - Peterschmidt, Betsy (2021)
"To prove that she is worthy of becoming a pilot, Amelia Erroway sets off alone on her father's prized craft until a fierce storm crashes her ship and she must use her wits to survive--and find a way home."--BTCat.
Ages 8-12 Grades 3-7
Keywords: Women air pilots -- Comic books, strips, etc; Fathers and daughters -- Comic books, strips, etc; Castaways -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Graphic novels -- United States; Action and adventure comics; Comics (Graphic works); Fiction; Graphic novels; Juvenile works; Action and adventure comics; Graphic novels; Comics (Graphic works); Fiction